The Introduced Australian Oyster Blenny, Omobranchus anolius - Barker, Jeremy James (Auckland University of Technology, 2009)
In 2003, an intertidal fish, the Australian oyster blenny (Omobranchus anolius) was discovered in Auckland, New Zealand. Subsequent surveys of the inner Hauraki Gulf found only 24 specimens, the majority of which (n=20) occurred at a single location within Tamaki River. Most non-indigenous species do not establish viable populations, few of those that do spread; even fewer become abundant and widespread and have negative ecological impacts. Little was known about the ecology of this fish, it was unclear whether it would establish and spread in New Zealand, and in the event it did, what effect it would have on native flora and fauna.
Keywords: Omobranchus anolius; Blenniidae; Invasive; Fish; Non-indigenous; Introduced